Hydrothermal liquefaction bioproduct of food waste conversion as an alternative composite of asphalt binder. (1st February 2021) - Mahssin, Zakariya Y.; Zainol, Muzakkir Mohammad; Hassan, Norhidayah Abdul; Yaacob, Haryati; Puteh, Mohd Hafiz; Saidina Amin, Nor Aishah
Abstract: Considerable environmental concern regarding increased food wastage caused by population and economic growth has been raised worldwide. The verification of food waste recycling product for engineering purposes is also vague. This work evaluates a liquefied bio-product recovered from the hydrothermal liquefaction of food waste as a potential non-petroleum-based binder in asphalt pavement. Various parameters were evaluated to optimize the liquefaction reaction for the enhancement of the liquefied food waste (LFW) product recovered from the process. The LFW was characterized for chemical compound and used to substitute different portions of conventional asphalt binders 60/70 pen (i.e., 10%, 20%, and 30%) from the total binder weight. The conventional and modified asphalt binders were evaluated for storage stability, physical and chemical properties, thermal decomposition, and functional groups. Thermal degradation affirms the presence of LFW in the modified asphalt, and the low molecular weight concerning high-boiling point compounds were identified. The use of LFW in the asphalt binder produces a modified binder with physical properties and storage stability that are comparable with those of petroleum-based asphalt, thereby suggesting that the liquefied product obtained from food waste can be used as bio-binder in asphalt pavement. Graphical abstract: Image 1 Highlights: Liquefied food waste can be used as alternative bio-binder in asphalt pavement. High viscosity and thermally stable liquefied product is physically mixed with asphalt. High substitution of liquefied food waste (up to 30%) in asphalt binder. Characteristics of bio-binder are comparable to conventional asphalt binder.